2020
DOI: 10.3923/jps.2020.64.73
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Compost/Soil Ratios for Sustainable Production of Garlic (Allium sativum L.) under Mycorrhization in Pots Experiment

Abstract: Background and Objective: Garlic are highly dependent on AMF but little is known about the appropriate compost/soil ratio that can boost crop growth and development under AMF inoculation. The present work was carried out in pots experiment at Dang-Ngaoundere to assess the effect of different compost/soil ratios inoculated with Arbuscular Mycorrhiza Fungi (AMF) on Allium sativum L. production. Materials and Methods:The experimental design was a randomized complete block comprising seven treatments, each of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Regarding the link between soils and mycorrhizal parameters, our observations confirm the results of Ngakou et al (2020) who showed that a substrate composed of 2/3 soil and compost added to 30g mycorrhizae is ideal for garlic production by mycorrhizal fertilisation. For the distribution of mycorrhizal spores in the study site, Tobolbaï et al (2018) obtained similar results, reporting that Glomus constrictum is the most abundant specimen in the rhizosphere of maize grown in North Cameroon.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the link between soils and mycorrhizal parameters, our observations confirm the results of Ngakou et al (2020) who showed that a substrate composed of 2/3 soil and compost added to 30g mycorrhizae is ideal for garlic production by mycorrhizal fertilisation. For the distribution of mycorrhizal spores in the study site, Tobolbaï et al (2018) obtained similar results, reporting that Glomus constrictum is the most abundant specimen in the rhizosphere of maize grown in North Cameroon.…”
Section: Discussionsupporting
confidence: 88%
“…These interactions can be very beneficial for plants, as is the case of the symbiotic plant-fungus endomycorrhizal association (Alabouvette andCordier, 2018, Diedhiou et al, 2022). Indeed, the fungal strains involved in this symbiosis are capable of improving the plant partner's hydro-mineral nutrition (Lambers et al, 2008), drought resistance (Leyval, 2005), yield (Ngakou et al, 2007;Ngakou et al, 2020), resistance to pathogens and pests (Elsen, 2003), and nutrition in polluted environments (Chen et al, 2007, Koffi et al, 2021. In addition, these micro-organisms stabilise soil aggregates by releasing a protein substance called glomalin (Rillig and Steinberg, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Togo, inoculation of soybean plants with mycorrhizae resulted in an improvement in plant height from 14 to 32 cm [54]. Also, the work of Ngakou et al [55] on garlic plants inoculated with mycorrhizae under greenhouse conditions observed an improvement in plant growth from 4.85 cm to 6.28 cm. Ogou et al [54] obtained in Togo an average mycorrhizae-induced pod gain on soybean of +126.83% compared to the control.…”
Section: Infected Corn Roots Colonized By Shrub-shaped Mycorrhizal Fu...mentioning
confidence: 99%